Platelet Modulation of Neutrophil Superoxide Anion Production - Moon, Dudley G; Zee, Hoyte van Der; Weston, Lisa K; Gudewicz, Paul W; Fenton II, John W; Kaplan, John E (Thrombosis and Haemostasis, 1990)
The effect of platelets on polymorphonuclear leukocytes (PMN) O−2 production was examined using autologous sheep and human cell systems. Coincubation of sheep platelets with sheep PMNs in the absence of thrombin resulted in a significant inhibition in basal PMN O−2 production. The platelet-derived inhibitory activity was released into the medium and could be destroyed by adenosine deaminase suggesting that the inhibitor was adenosine. Addition of alpha-thrombin or platelet activating factor (PAF) enhanced PMN O−2 production but only when platelets were present. The enhancement of O−2 production in response to thrombin was dependent upon the thrombin concentration and the platelet-PMN ratio. With a platelet:PMN ratio of 30:1, addition of 10 nM thrombin to sheep cells resulted in a 5-fold increase in O−2 production, whereas addition of 10 nM PAF caused a 2-fold increase in O−2. Addition of thrombin or PAF to either PMNs or platelets by themselves did not initiate an increase in O−2 generation. The response of human cells was similar except that both thrombin and PAF triggered a 2-fold increase in PMN O−2 production in the presence of platelets. The platelet-derived enhancement activity was not released into the medium and was not blocked by WEB 2086, NDGA, ETYA, aspirin or adenosine deaminase. The enhancement effect appeared to be localized to the platelet membrane and we believe requires platelet-PMN contact.
Keywords: Platelet; neutrophil interactions; Oxygen radicals